2015
DOI: 10.1007/s00408-015-9728-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Predictors of Rebleeding After Bronchial Artery Embolization in Patients with Active or Inactive Pulmonary Tuberculosis

Abstract: The risk of rebleeding after BAE in active or inactive PTB was high, particularly in patients with tuberculous-destroyed lung, chronic liver disease, the use of anticoagulant agents and/or antiplatelet agents, elevated pre-BAE CRP, and the existence of fungal ball.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
3
19
1
1
Order By: Relevance
“…None of the patients suffered from major complications such as spinal cord injury. CT and angiographic findings are concordant with Kim et al including ground-glass opacity (72 %) and consolidation (61 %) as the most-specific findings for pulmonary bleeding in CT, and neo-vascularization (85 %) and vessel hypertrophy (45 %) as typical angiographic findings [10]. Active bleeding in angiographic images occurred in only 16 % of cases and should not be used for decision-making for BAE procedure.…”
supporting
confidence: 74%
“…None of the patients suffered from major complications such as spinal cord injury. CT and angiographic findings are concordant with Kim et al including ground-glass opacity (72 %) and consolidation (61 %) as the most-specific findings for pulmonary bleeding in CT, and neo-vascularization (85 %) and vessel hypertrophy (45 %) as typical angiographic findings [10]. Active bleeding in angiographic images occurred in only 16 % of cases and should not be used for decision-making for BAE procedure.…”
supporting
confidence: 74%
“…[22,27,29] In the present study, the recurrence rate in patients with CPA was 55%, which is approximately two times higher than that of TB patients. [23,2729] In addition, the majority of patients with recurrence of hemoptysis required repeat BAE. Therefore, additional treatments after a successful BAE are recommended to ensure the long-term success of the embolization in CPA patients.…”
Section: Discussionmentioning
confidence: 66%
“…[26] Numerous studies have demonstrated the effectiveness and success of BAE, especially in TB patients. [23,2729] However, the recurrence of hemoptysis following successful BAE remains common and is associated with aspergilloma. [22,27,29] In the present study, the recurrence rate in patients with CPA was 55%, which is approximately two times higher than that of TB patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al, 2007) that patients with pulmonary TB history have a signi cantly higher number of total culprit arteries and culprit NBSAs than patients without pulmonary TB history [44]. According to prior studies, hemoptysis recurrence after BAE tended to be higher in patients with TB (chronic or active/reactivated TB) [37,41,44,45]. These outcomes are contrary to the current study, which has reported that pulmonary TB history was not related to re-bleeding.…”
Section: Discussionmentioning
confidence: 99%